THE ROLE OF ENVIRONMENTAL RESPONSIBILITY IN MAXIMIZING THE VALUE OF THE COMPANY (World Economics and Finance Bulletin, 2022)
The study aimed to study and analyze the relationship between environmental responsibility and its impact on maximizing the value of the company; As well as drawing attention to the environmental impacts caused by industrial companies as a result of their industrial activity, which necessitates making more efforts to reduce the level of environmental problems .The study reached some conclusions, including, that the concept of environmental responsibility is summed up as “all obligations and activities performed by industrial companies towards the internal environment and the external environment to reduce the risk of environmental pollution and to determine all these commitments from a financial point of view for the purpose of reporting them in financial reports and delivering them to stakeholders for the purpose of taking appropriate decisions. The study recommended obligating industrial companies to disclose their environmental and social responsibility within the financial statements they issue for the purpose of knowing the size of spending on environmental responsibility and their contribution to reducing environmental problems
Keywords: Environmental Responsibility; Environmental Pollution; Value of Company